Progesterone supplementation in women with threatened miscarriage: narrative review - Ratnaningtyas, Lucia Shinta; Dedeo, Yermia Ademi; Lintarsari, Gustia Alinda; Kusmiyati; Vifiladya, Maulidina (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2025)
The effectiveness of progesterone supplementation in treating impending miscarriages is still debatable. This narrative review aimed to evaluate the effectiveness of progesterone for pregnant women who are at risk of miscarriage. The effectiveness of progesterone were obtained from online database publications as PubMed, EBSCOhost, and Google Scholar between 2019 and 2024. The search was conducted by entering keywords in the database. Then by screening titles, abstracts, and contents, the search result obtained 15 articles. The outcomes were miscarriage, preterm birth, and live birth. Eight RCTs, 1 cohort, 5 meta-analyses, and 1 systematic review were included in this narrative review. The RCTs reviewed, revealed several journals which mention that oral, vaginal, and placebo progesterone have not significantly differed in preventing miscarriage. However, there were RCTs journal mention that oral dydrogesterone, vaginal and oral progesterone are effective in preventing miscarriage. In contrast, a meta-analysis research indicated that oral progesterone, vaginal progesterone, and dydrogesterone were all effective in reducing miscarriage. Progesterone supplementation may be effective in women at risk of miscarriage. The recommended route of progesterone treatment to threatened miscarriage is still controversial, but based on this narrative review, the vaginal route of progesterone is more effective and safer than oral route.